The influence of audit opinion, characteristics of regional head, and levels of corruption on performance of local government in Indonesia - Angelina, Junita; Saerang, David Paul Elia; Warongan, Jessy D. L. (The Contrarian : Finance, Accounting, and Business Research, 2024)
This study aims to analyze the influence of audit opinion, characteristics of regional head, and the level of corruption on local government performance in Indonesia. This study uses secondary data with the research population being all local governments in Indonesia with a research sample of 394 observations in 2021. The analysis method used is multiple linear regression analysis. The results of multiple linear regression test show that audit opinion and the education level of the regional head have a positive and significant effect on local government performance. Meanwhile, the experience of the regional head and the level of corruption have a negative and significant effect on local government performance. However, it is known that the age of the regional head has no significant effect on local government performance. This study implies that the better the audit opinion, the better the local government performance, as well as the higher the education level of the regional head, the higher the cognitive complexity possessed by the regional head can further improve local government performance. This study also shows that there is a negative effect on the experience of regional heads and the level of corruption on local government performance. This implies that regional heads with experience as non-bureaucrats can improve local government performance more than regional heads with experience as bureaucrats. In addition, the negative effect of the level of corruption on local government performance implies that the higher the level of corruption that occurs in a region, the worse the performance of the local government. As for the age of the regional head, it is not statistically proven to affect local government performance, this finding reveals that other factors such as experience and education level may be more decisive.